Deep in the Diphthong Problem: A Study on Indonesian EFL Learners’ Pronunciation Development and the Influence of Individual Differences - Feisal Aziez; Intan Sofiana (Fakultas Bahasa dan Seni UNP, 2023)
The current study aims at investigating the development of Indonesian EFL learners' pronunciation in terms of diphthong. In this study learners' pronunciation were observed over a period of six months to see how they develop. Moreover, the influence of their linguistic background on the pronunciation development was also measured namely age of acquisition, native language, level of English accent and the extend of English exposure. The data of this study was collected using pronunciation tests and the Language History Questionnaire (LHQ). The participants involved in this research were 25 university English students who were taking Phonetics course. The collected data was then analyzed using SPSS. The analysis techniques of this study were descriptive statistics and multiple regression analysis. The study found that the learners' diphthong pronunciation did not develop significantly. Moreover, it even tends to have downward trend. Finally, according to the regression analysis, the aspect of learners' linguistic background that affected the most on their pronunciation development was their exposure to English.